Nature-based solutions for Mahanadi River basin protection and conservation - Mishra, Ajay Kumar; Mishra, Sarita; Sahoo, Manas Ranjan; Sharma, Sheetal (Springer, Singapore, 2025)
The Mahanadi River Basin, a critical ecosystem in East Central India, supports millions of people through agriculture, fisheries, and freshwater resources. However, this basin faces several environmental challenges, including pollution, soil erosion, deforestation, and the adverse impacts of climate change. Nature-based solutions (NbS) offer a sustainable approach to address these issues by leveraging natural processes to restore ecosystems, mitigate floods, enhance water quality, and promote biodiversity. This chapter explores the potential of NbS for the conservation of the Mahanadi River Basin. Specific strategies such as riparian buffer zones, wetland restoration, sustainable agriculture, and community-led watershed management are discussed. By integrating these solutions into development planning, NbS can provide long-term environmental and socioeconomic benefits, including improved soil health, enhanced biodiversity, and climate resilience. This chapter emphasizes the importance of stakeholder engagement, community participation, and policy support in successfully implementing NbS in the Mahanadi River Basin to ensure its ecological and economic sustainability.